2009
DOI: 10.1007/s10211-009-0056-7
|View full text |Cite
|
Sign up to set email alerts
|

Usage of monophonic and biphonic calls by free-ranging resident killer whales (Orcinus orca) in Kamchatka, Russian Far East

Abstract: Killer whale discrete calls include types containing an overlapping high-frequency component (biphonic calls) and types without an overlapping high-frequency component (monophonic calls). In the resident killer whales of the Northeast Pacific, biphonic discrete calls exhibit higher source levels than monophonic calls, which suggests different active space and consequently different functions for monophonic and biphonic call types. In this study we investigate the potential communicative functions of monophonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 33 publications
(57 reference statements)
0
47
2
Order By: Relevance
“…Biphonations are common, specifically in the form of lower-frequency burst-pulse sounds together with higherfrequency, independent FM components [203,213,214,220,223]. Populations along the Canadian British Columbia coast have been studied extensively using passive acoustics.…”
Section: Orcinus Orca-killer Whalementioning
confidence: 99%
See 1 more Smart Citation
“…Biphonations are common, specifically in the form of lower-frequency burst-pulse sounds together with higherfrequency, independent FM components [203,213,214,220,223]. Populations along the Canadian British Columbia coast have been studied extensively using passive acoustics.…”
Section: Orcinus Orca-killer Whalementioning
confidence: 99%
“…Their sounds have been studied in coastal British Columbia, Canada, and Washington State, USA [201][202][203][204][205][206][207][208][209][210], in California [211], in other areas of the North Pacific, including Russia [212][213][214][215][216], in the North Atlantic off Norway and Iceland [217,218], in Antarctica [219,220] and south-western Australia [16]. A geographic comparison of North Atlantic and North Pacific killer whale sound frequencies was recently published [221].…”
Section: Orcinus Orca-killer Whalementioning
confidence: 99%
“…Methods in most common use range from t-tests, ANOVA and Chi-square tests or non-parametric equivalents to regression models (Deecke et al 2005, Filatova et al 2009, Foote et al 2004, Lemon et al 2006, Luís et al 2014, Oleson et al 2007, Sjare and Smith 1986, from simple linear models to those incorporating smooth terms, random effects and generalized estimating equations (Quick and Janik 2008, DeRuiter et al 2013, Di Iorio and Clark 2010, Stimpert et al 2015, Visser et al 2016. Other authors use randomization-based methods Solow 2008, Miller et al 2009) or machine-learning classification methods such as random forest decision trees [Henderson et al 2012].…”
mentioning
confidence: 99%
“…Both biphonic and monophonic call types were used in the vocal responses of killer whale groups on the playbacks of recordings from the same pod. In Kamchatkan killer whales, monophonic calls prevail in intrapod communication, and the rate of biphonic calls increases when more than one pod is present (Filatova et al . 2009 a ).…”
Section: Discussionmentioning
confidence: 99%
“…2007, Foote et al . 2008, Filatova et al . 2009 a ) showed that the usage of different call types depended more on the presence of other pods or matrilines rather than on the type of activity.…”
mentioning
confidence: 99%